Interactions Between Tumor Biology and Targeted Nanoplatforms for Imaging Applications. (3rd March 2020) - Azizi, Mehdi; Dianat‐Moghadam, Hassan; Salehi, Roya; Farshbaf, Masoud; Iyengar, Disha; Sau, Samaresh; Iyer, Arun K.; Valizadeh, Hadi; Mehrmohammadi, Mohammad; Hamblin, Michael R.
Abstract: Although considerable efforts have been conducted to diagnose, improve, and treat cancer in the past few decades, existing therapeutic options are insufficient, as mortality and morbidity rates remain high. Perhaps the best hope for substantial improvement lies in early detection. Recent advances in nanotechnology are expected to increase the current understanding of tumor biology, and will allow nanomaterials to be used for targeting and imaging both in vitro and in vivo experimental models. Owing to their intrinsic physicochemical characteristics, nanostructures (NSs) are valuable tools that have received much attention in nanoimaging. Consequently, rationally designed NSs have been successfully employed in cancer imaging for targeting cancer‐specific or cancer‐associated molecules and pathways. This review categorizes imaging and targeting approaches according to cancer type, and also highlights some new safe approaches involving membrane‐coated nanoparticles, tumor cell‐derived extracellular vesicles, circulating tumor cells, cell‐free DNAs, and cancer stem cells in the hope of developing more precise targeting and multifunctional nanotechnology‐based imaging probes in the future. Abstract : Interactions between tumor biology and targeted nanoplatforms for imaging applications are discussed based on passive enhanced permeability and retention targeting, active targeting to hypoxia, low pH, angiogenesis, and cancer cell surface markers. Types of cancer include, breast, lung, colorectal, prostate, pancreatic, bladder, brain, and ovarian. Future directions include membrane‐coated nanoparticles tumor cell–derived extracellular vesicles, circulating tumor cells, cell‐free DNAs, and cancer stem cells.